Challenging the Norms and Law: Reconstructing Social Injustice and Creating an Equitable Society - Arief Fahmi Lubis (Penelitian dan Pengembangan Ilmu, 2024)
The challenge of challenging existing norms and laws to correct social injustice and promote equality is a complex and multidisciplinary topic. In this context, it is important to consider the intersection of accountability, law, citizenship and indigenous rights. This research focuses on a systematic literature review to explore how identity perspectives, such as ethnicity, gender, and social class, influence perceptions of norms and laws, and their contribution to social injustice. Through this approach, researchers aim to present a more comprehensive understanding of the complexity of the relationship between social identity and social injustice, as well as providing a solid foundation for further development. It is hoped that this research can make a significant contribution to our understanding of the factors that influence social injustice, as well as enrich insight into the efforts that can be taken to achieve more inclusive and sustainable social justice.